2015
DOI: 10.4108/icst.pervasivehealth.2015.259064
|View full text |Cite
|
Sign up to set email alerts
|

BioWatch: Estimation of Heart and Breathing Rates from Wrist Motions

Abstract: Abstract-Continued developments of sensor technology including hardware miniaturization and increased sensitivity have enabled the development of less intrusive methods to monitor physiological parameters during daily life. In this work, we present methods to recover cardiac and respiratory parameters using accelerometer and gyroscope sensors on the wrist. We demonstrate accurate measurements in a controlled laboratory study where participants (n = 12) held three different positions (standing up, sitting down … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 23 publications
2
74
0
1
Order By: Relevance
“…We used an fNIRS device, which has been shown to be suitable for HCI user study evaluations, but more commercially available devices like the NeuroSky 4 EEG device might be more suitable for day to day feedback. Similarly, even less invasive measures of mental workload could be taken from Heart Rate Variability [24] through smart watches, remotely detected by pupil dilation [33] or facial skin temperature [53] with cameras. Many of these other measures also better detect emotional responses, and perhaps concepts like stress and anxiety, and so might better serve future work on recording both Mental Workload and emotional response.…”
Section: Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We used an fNIRS device, which has been shown to be suitable for HCI user study evaluations, but more commercially available devices like the NeuroSky 4 EEG device might be more suitable for day to day feedback. Similarly, even less invasive measures of mental workload could be taken from Heart Rate Variability [24] through smart watches, remotely detected by pupil dilation [33] or facial skin temperature [53] with cameras. Many of these other measures also better detect emotional responses, and perhaps concepts like stress and anxiety, and so might better serve future work on recording both Mental Workload and emotional response.…”
Section: Future Workmentioning
confidence: 99%
“…There are a variety of subjective and objective methods used for measuring mental workload, including primary and secondary task analysis [40], physiological or psycho-physiological techniques [24,33,44,52], as well as user opinions using subjective techniques [23,31]. The most commonly used method for mid-task workload monitoring in industry, as a form of secondary task analysis, is ISA (Instantaneous Self Assessment) and relies on people self reporting their levels of workload at time intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable devices were successfully used as monitoring and alerting systems in case of highrisk cardiac patients [13], of analysing Parkinson patient's movement for detecting and preventing freezing of gait [14] and for estimations of heart and breathing rates from wrist motions [15]. The newest generation of smartwatches is now capable of measuring the HR very accurately with the help of photoplethysmography (PPG) technology [16].…”
Section: B Wearable Devicesmentioning
confidence: 99%
“…These algorithms are motivated by our previous work [7][8] [15], which considered different datasets and modalities to extract physiological parameters. The methods were adjusted to be able to correct undesired motion artifacts (e.g., different window sizes) and capture more subtle motions (e.g., lower filter orders).…”
Section: B Accelerometer Processingmentioning
confidence: 99%
“…In recent work [7][8], we have demonstrated that motion sensors embedded in head-mounted and wrist-worn wearable devices such as Google Glass and Galaxy Gear can capture heart and breathing rates accurately. While the results were very promising, not everybody uses these types of wearable devices as they may be cumbersome and stigmatizing.…”
Section: Introductionmentioning
confidence: 99%